2015
DOI: 10.1007/s11517-015-1283-x
|View full text |Cite
|
Sign up to set email alerts
|

The shape of dementia: new measures of morphological complexity in event-related potentials (ERP) and its application to the detection of Alzheimer’s disease

Abstract: In this paper, we address the problem of quantifying the commonly observed disorganization of the stereotyped wave form of the ERP associated with the P300 component in patients with Alzheimer's disease. To that extent, we propose two new measures of complexity which relate the spectral content of the signal with its temporal waveform: the spectral matching coefficient and the spectral matching entropy. We show by means of experiments that those measures effectively measure complexity and are related to the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Among previous studies that have explored various ERP features for the discrimination of AD from normal individuals, Jimenez‐Rodriguez et al 31 . extracted SMC and SSME features and reached a sensibility of 81% and a specificity of 85%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among previous studies that have explored various ERP features for the discrimination of AD from normal individuals, Jimenez‐Rodriguez et al 31 . extracted SMC and SSME features and reached a sensibility of 81% and a specificity of 85%.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to develop a diagnostic procedure that discriminates between AD and age‐matched control individuals, Jimenez‐Rodriguez et al 31 . proposed two novel measures of complexity of the shape in time series: spectral matching complexity (SMC) and spectral matching entropy (SSME).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerably important is the fact that individuals with MCI have an increased risk of developing Alzheimer’s disease (AD) [2,4]. AD is the most common form of dementia, characterized by a progressive deterioration of cognitive function due to widespread neuronal loss and synaptic dysfunction, accompanied by extracellular amyloidosis and intracellular tangle formation [5]. Current literature suggests that patients with MCI progress to AD at a rate of 10% to 15% per year, and 80% of these patients converted to AD after approximately 6 years of follow-up [2].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, much effort has been dedicated to the early clinical diagnosis of dementing disorders with the aim of identifying factors associated with AD [6]. Most of the studies have mainly focused on the association of cognitive decline with biomarkers obtained by neuroimaging and from cerebrospinal fluid [4,5,7,8]. However, it has been demonstrated that cognitive deterioration, accumulation of amyloid-β (Aβ) and tau protein are not equivalent and not linear with respect to disease progression and the appearance of its cognitive symptoms [9].…”
Section: Introductionmentioning
confidence: 99%